2018
DOI: 10.1155/2018/1317436
|View full text |Cite|
|
Sign up to set email alerts
|

High‐ and Low‐Temperature Properties and Thermal Stability of Silica Fume/SBS Composite‐Modified Asphalt Mortar

Abstract: Recently, China has started paying more attention to environmental protection, and the efficient utilization of exhaust gases produced by smelting has emerged as a key problem concern. e silica fume collected from the exhaust gases produced by smelting ferrosilicon or industrial silicon was often used as a cement concrete admixture. Using silica fume as an asphalt modifier can make exhaust gases profitable. In this study, silica fume/SBS composite-modified asphalt mortar was prepared to improve the performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Cone penetration test indicates the ability of asphalt to resist shear deformation 26–28 . When the fiber is mixed with asphalt, it absorbs the free oil in the asphalt and forms a complex spatial network in the asphalt 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cone penetration test indicates the ability of asphalt to resist shear deformation 26–28 . When the fiber is mixed with asphalt, it absorbs the free oil in the asphalt and forms a complex spatial network in the asphalt 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Cone penetration test indicates the ability of asphalt to resist shear deformation. [26][27][28] When the fiber is mixed with asphalt, it absorbs the free oil in the asphalt and forms a complex spatial network in the asphalt. 29 The tip of the standard needle used in the general experiment is much smaller than the size of the fiber itself, which can affect the test results with high degree of deviation.…”
Section: Cone Penetration Testmentioning
confidence: 99%
“…A review of past literature [ 4 , 27 ] revealed that the low temperature performance of asphalt will greatly reduce when the silica fume content exceeds a certain level. After comprehensive consideration of previous research [ 28 , 29 ], the silica fume content with mass fractions of 2%, 4%, 6%, and 8% of asphalt was selected in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies indicated the use of the various additives in SMA apart from cellulose fiber [4-6, 9, 11, 13-15]. Different research demonstrated the evaluation of |E * | and development of master curves [14,[16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Literature Reviewmentioning
confidence: 99%